Combination of Qur'anic Murrotal and Deep Breath Relaxation Against Post Sectio Caesarea (Sc) Pain Changes - Kustin, Kustin; Nurdiana, Didin (Journal of Nursing Periodic, 2024)
Sectio Caesarea (SC) surgical procedure will have an impact on damage at the tissue level to the nerves that cause postoperative wounds in the incision area which results in pain. Non-pharmacological complementary therapies may be an option that can be done by nurses to manage the pain of SC postoperative patients. The purpose of this study is to determine the effect of the combination of Qur'an Murotal therapy and deep breath relaxation on the pain of post-SC patients at Jember Clinic Hospital in 2023. The design of this study was a pre-experiment with the one group pretest-posttest method. The research sample was 45 respondents with accidental sampling technique. The Visual Analog Scale (VAS) is used to measure pain. Bivariate analysis using parametric paired t-test. Result of this study was the average score of postoperative SC patients before the intervention of a combination of Qur'anic Murotal therapy and breath relaxation was 6.76. The average score of pain levels in SC postoperative patients after a combination intervention of Qur'anic Murotal therapy and breath relaxation was 4.73. The paired t-test results obtained a value of p = 0.000 which means Ha is accepted which means there is an effect of combination therapy of Murotal Qur'an therapy and deep breath relaxation on the pain of post-SC patients at Jember Clinic Hospital.